The Influence Of Online Customer Reviews And Influencer Marketing On The Originote Skincare Product Purchase Interest On Tiktok - Safitri, Dian Ayu; Fitriyah, Zumrotul (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
Products that can make facial skin healthier and glowing. One of the local beauty industry brands is the originote, The originote has beauty products, one of the viral products is serum. The marketing strategy carried out by the originote is with Online Customer Review and Influencer Marketing. This study aims to determine the influence of Online Customer Review and InfluencerMarketingon purchase Interest of The Originote Skincare Products on TikTok. This research method uses a quantitative method. The population in this study were TikTok application users who knew about The Originote Skincare products. Sampling was done by purposive sampling which was calculated using the Ghozali formula with a total of 126 respondents. The analysis technique used in this study was SEM-PLS using SmartPLS 4. The results showed that online customer reviews and influencer marketing each had a significant influence on purchase interest in The Originote skincare on TikTok.